2008
DOI: 10.1128/cvi.00165-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Commercial Immunoblot, Helicoblot 2.1, for Diagnosis of Helicobacter pylori Infection

Abstract: The best method to diagnose Helicobacter pylori infection in different clinical situations is controversial. The aim of the study was to assess the performance of a commercial immunoblot, Helicoblot 2.1. The study comprised 215 patients, who were grouped according to the presence of H. pylori infection (assessed by two gastroscopies including histology with a median interval of 7.1 years, enzyme immunoassay [EIA]-based serology, and history of previous H. pylori infections and eradication therapies) into four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
4
15
0
Order By: Relevance
“…There are two plausible explanations for this finding. First, the difference in seropositivity of CagA (75.6%) and of the screening ELISA (66.1%) in GC cases suggests that CagA may have a much stronger antigenicity compared with some other immunogenic proteins, and thus, antibodies against it persist longer after clearance of the infection (23)(24)(25)(26). Second, as shown in Table 6, lower proportions of CagApositive strains were observed among H. pylori-infected controls compared with H. pylori-infected GC cases.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…There are two plausible explanations for this finding. First, the difference in seropositivity of CagA (75.6%) and of the screening ELISA (66.1%) in GC cases suggests that CagA may have a much stronger antigenicity compared with some other immunogenic proteins, and thus, antibodies against it persist longer after clearance of the infection (23)(24)(25)(26). Second, as shown in Table 6, lower proportions of CagApositive strains were observed among H. pylori-infected controls compared with H. pylori-infected GC cases.…”
Section: Discussionmentioning
confidence: 87%
“…There is evidence that antibodies to CagA can persist longer after the eradication of H. pylori infection and estimates of the association between Table 4. Backward stepwise multivariate logistic regression exposure to H. pylori and GC were highly increased when CagA serostatus was considered combined with the screening ELISA (25). To our knowledge, the present study is the first epidemiologic study on GC risk simultaneously investigating antibodies to 15 different H. pylori proteins using multiplex serology.…”
Section: Discussionmentioning
confidence: 93%
“…Interesting, among the 13 false negative samples obtained with the Western-rCagA, 9 were classified as H. pylori negative CagA positive by HB 2.1. It is though that CagA seropositivity in H. pylori-seronegative subjects may either be a sign of a past H. pylori infection due to the long life of anti-CagA antibodies (18,28) or represent a false positive reaction (29). Therefore, probably the rCagA of this study may not contain the epitopes causing either of the above mentioned events that should be, if demonstrated, an advantage of this recombinant fragment to diagnose CagA-positive H. pylori infection.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies using diagnostic methods to detect CagA antibodies have demonstrated that this antigen improve the sensitivity of H. pylori detection (18). Also, it has been observed that the positivity for CagA antibodies has the ability to predict the development of atrophy and appears related with young gastric cancer cases (10).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, serum IgG to H. pylori Cag A antigen persists for a long time after H. pylori disappearance 10 , in some cases for several decades. According to Veijola et al 11 , anti-Cag A IgG levels decrease only slightly after a number of years, and 87 of patients remain positive after 10 years. In the present study we showed that the antibody titer of patients with previous H. pylori infection is higher than that of patients naïve to H. pylori infection, although the antibody titer after H. pylori disappearance may decrease over time to below the limit of detection.…”
Section: Discussionmentioning
confidence: 99%